Paediatric Intussusception in Dar es Salaam, Tanzania (Tanzania Medical Journal, 2015)
Background: Intussusception is a common cause of intestinal obstruction in children below 5 years of age. Prompt diagnosis and treatment reduce its morbidity and mortality in Sub-Saharan Africa.Broad objective: To describe the socio-demographic and clinical characteristics of intussusception in infants and children in local settings during a nine-year period and determine the incidence in infants up to 12 months of age. Methodology: This is a retrospective study whereby the medical records of all infants and children up to the age of 5 years diagnosed to have intussusception and admitted at the paediatric surgical ward at Muhimbili National Hospital (MNH) from January 2000 to December 2008 were reviewed. Demographic factors evaluated included age, sex, month of presentation to assess any seasonal variation, etiology, clinical features, duration of symptoms, methods of diagnosis and management, outcome including mortality.Results: During the nine-year period, 73 children were diagnosed to have intussusception. 48 were males and 25 females (M: F=1.9:1). The infant group (up to the age of one year) was 58 (79.5%), 34 were boys and 24 girls (M: F=1.4:1). Most cases presented in January-March (31. 5%) and July to September (39.7%) which were the dry seasons. All patients presented with vomiting and abdominal distention. History of preceding gastro- enteritis was seen in the infant group. The majority, 59 cases (80.8%) presented with the classic triad of vomiting, passing red currant jelly stools and abdominal distention. Abdominal mass was palpated in only 11 cases (15.1%) as patients presented late with very distended and tense abdomen.7 cases (12.1%) presented with anal protrusion of the intussusceptum, which was associated with poor prognosis. Diagnosis was mainly made clinically and all children were managed by emergency laparotomy. Majority were found to be ileo-colic type. Twenty nine (39.7%) underwent bowel resection due to perforation with or without gangrene of the intussuscepted bowel. Twenty-three patients died postoperatively, a mortality of 31.5%.Conclusion: The intussusception rate in babies up to one year old was calculated to be approximately 1:7500 but this is an underestimate as records were missing and some die before getting to hospital.